Ecobrick Sofa Design Is Environmentally Friendly Using The House Of Quality Method And The Boston Consulting Group (Bcg) Method - utami, Arie; Johan, Johan; Prasetyo, Tri Budi; Amalia, Mia (Ann Publisher, 2024)
Plastic is one of the longest decomposing types of waste with a decomposition time of up to 10 centuries. Plastic waste that is difficult to decompose can be minimized by using ecobrick techniques. This ecobrick technique aims to turn plastic waste that was initially worthless (zero value) into a product that has added value. This study uses four methods, namely the House of Quality (HOQ), Quality Function Deployment (QFD), Slovin, and Boston Consulting Group (BCG) methods. These methods are used to determine product planning and development, consumer desires, product position in market share, and systematic evaluation of its ability to produce products to satisfy consumers. This study involved 100 respondents obtained from the slovin method. Where the respondents are positioned as research subjects. The respondent data was obtained from distributing questionnaires through google forms. The data collected is calculated and analyzed for unique and minimalist sofa House of Quality (HOQ). The results of this study inform that customer feedback on the product or Voice of Customer can affect quality control and improvement by using the statistical method or Statistical Quality Control. Furthermore, unique and minimalist sofa companies each have different product development focuses. Following up on the findings in this study, the company can adjust the needs and desires of these consumers to the design and service standards as well as the obstacles that may occur.